Estimativa da biomassa e nutrientes em espécies arbóreas da caatinga, Rio Grande do Norte - Silva, Erick Daniel Gomes da (Universidade Federal Rural do Semi-Árido, 2019)
Tropical native forests are on low fertility soils, and therefore make up complex ecosystems, supported by nutrient cycling and floristic diversity. The objective of this study was to quantify the biomass of the aerial part and to determine the nutrient content of three tree species in two forest remnants of the Brazilian Amazon. The objective of this study was to understand the relationship between the unmanaged exploitation of the caatinga and the development and self sustainability of the forest vegetation of this caatinga. Caatinga, in the region of Mossoró, Rio Grande do Norte. The research was carried out in two forest fragments of Caatinga near the municipality of Mossoró / RN, denominated area 1 and 2. For the biomass analysis, the forest inventories were used as base, and on top of this information were selected three species with greater representativeness in the areas and of economic importance for the region. Then five circumference classes were created and within these classes were sampled three individuals per species, totaling 15 individuals per species. The individuals were chosen in a random manner and each plant chosen had a measure of their circumference at breast height and at the base, crown projection area, total height and commercial height. For the process of weighing and sampling of the parts of the aerial part, the chosen trees were dropped, sectioned and weighed, and a sample of approximately 100 g was collected from each component to carry out the chemical analyzes. Regarding the results, Auxemma oncocalyx (Pau branco) presented a mean total height (HT) of 6.3 m and an average commercial height (HC) of 5.1 m for dry biomass was approximately 4.08 t ha-1, represented by 0.16 t ha-1 of leaves; 1.20 t ha-1 of twigs and 2.72 t ha-1 of stems. Meanwhile, Mimosa tenuiflora (Jurema negra) presented a mean HT of 5.4 m and a mean HC of 3.8 m, in relation to dry biomass, was approximately 4.12 t ha -1, represented by 0.24 t ha-1 of leaves; 1.54 t ha-1 of branches and 2.33 t ha-1 of stems. Poincianella pyramidalis (Catingueira) presented a mean HT of 4.5 m and a mean HC of 3.0 m for dry biomass was approximately 6.32 t ha-1, represented by 0.31 t ha-1 of leaves ; 2.51 t ha-1 of branches and 3.49 t ha-1 of stems. As regards nutrients, the NPK levels in g.kg-1 of the three species were (18.3 N, 1.0 P and 3.5 K) in Auxemma oncocalyx; (14.3 N, 1.0 P and 1.6 K) in Mimosa tenuiflora and (11.7 N, 1.7 P and 1.2 K) in Poincianella pyramidalis. The species presented considerable amount of biomass and carbon and the highest nutrient contents were observed in the leaf component, factors that indicate good potential of use in reforestation and commercial plantations. In the case of the exploitation of the timber resource, it is recommended that at the time of processing the leaves and thin branches should remain in the area to allow the cycling of the nutrients and the incorporation of these in the next cutting cycle.
Monografia
Keywords: Silvicultura; Reflorestamento; Manejo florestal; Macronutrientes; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL